1988
DOI: 10.1007/bf00737143
|View full text |Cite
|
Sign up to set email alerts
|

Renal amyloidosis

Abstract: Sixty-one autopsy cases of renal amyloidosis were reviewed to assess the relationship of renal pathology to chemical types of amyloid and clinical features. Glomerular amyloid deposition was divided on the basis of morphological characteristics, into four types: a mesangial nodular type showing nodular mesangial deposits with sparse capillary wall involvement (25 cases), a mesangio-capillary type disclosing diffuse amyloid deposition in the mesangium and along both sides of the glomerular basement membrane (19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…It is thought that amyloid deposition accelerates renal dysfunction [3, 13, 14]. Renal biopsy of patients with renal dysfunction showed that when total tubulointerstitial and vascular damage exceeded 4 points, renal damage was severe (table 4).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is thought that amyloid deposition accelerates renal dysfunction [3, 13, 14]. Renal biopsy of patients with renal dysfunction showed that when total tubulointerstitial and vascular damage exceeded 4 points, renal damage was severe (table 4).…”
Section: Discussionmentioning
confidence: 99%
“…Severe proteinuria and nephrotic syndrome are strongly related to the amount and pattern of amyloid deposition [13, 20]. Bohle et al [3]reported that tubulointerstitial damage in renal amyloidosis, especially interstitial fibrosis, was an important finding determining renal prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, the renal location of the amyloid deposition might be different in our patient and the previously reported patients. The clinical presentation and prognosis of renal AA amyloidosis were reportedly associated with whether the amyloid deposited predominantly in the glomeruli or in the vessels [15, 16]. Moreover, therapeutic response of DMARDs may vary among different renal cell types in patients with AA amyloidosis.…”
Section: Discussionmentioning
confidence: 99%